Influence of thermal and chemical pretreatment on structural stability of granular sludge for high-rate hydrogen production in an UASB bioreactor - Zinatizadeh, A.A.; Mirghorayshi, M.; Birgani, P.M.; Mohammadi, P.; Ibrahim, S. (Elsevier, 2017)
Fermentation of organic waste materials presents an alternate route instead of photosynthetic and chemical routes for hydrogen production. Low yield of biohydrogen production is the major challenge in the fermentative hydrogen-producing technology. Improvement of fermentation process by various sludge pretreatment methods is one of the ways that have been applied to boost hydrogen productivity. This study sheds new light on the impact of thermal and chemical pretreatments on the hydrogen-producing granular sludge morphology and strength as well as up-flow anaerobic sludge blanket (UASB) reactor performance treating palm oil mill effluent (POME). Thermal pretreatment showed devastating effects on the morphological and structural characteristics of the granules. However, the chemically pretreated granules remained structurally stable and relatively undamaged. The thermal pretreatment increased the cumulative hydrogen production by 40% and 76% over chemical pretreatment and control test (untreated), respectively.